2021
DOI: 10.2174/1574885516666210510185538
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of Temozolomide, Metformin, and Epigallocatechin Gallate Promotes Oxidative Stress-Induced Apoptosis in Glioma Cells

Abstract: Aim: To study the synergistic anti-glioma efficacies of Temozolomide, Metformin and Epigallocatechin Gallate in U87MG and C6 glioma cells. Background: Glioblastoma (GBM) is the most malignant and invasive tumor of the central nervous system. The current standard treatment comprises surgical resection, followed by adjuvant radiotherapy and chemotherapy employing temozolomide (TMZ). Yet the survival rates for GBM patients is very low. Hence there is a need for new treatment regimes Objective: This study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This study was conducted on nine series of experimental groups (n = 48), namely, Group I: Normal rats without tumor induction (Control “C”) (n = 3); Group II: Tumor-control (TC) (n = 3); Group III: T-treated glioma-induced rats “(T)” (n = 6); Group IV: M-treated glioma-induced rats “(M)” (n = 6); Group V: E-treated glioma-induced rats “(E)” (n = 6); Group VI: TM-treated glioma-induced rats (TM) (n = 6); Group VII: TE-treated glioma-induced rats (TE) (n = 6); Group VIII: ME-treated glioma-induced rats (ME) (n = 6) and Group IX: TME-treated glioma-induced rats (TME) (n = 6) as shown in Figure 1A . The dosage of the drugs, either alone or in combination, to be administered to the rats were selected based on our in vitro data and previous studies in glioma ( Fernandes et al, 2017 ; Yu et al, 2017 ; Piwowarczyk et al, 2020 ; Kuduvalli et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted on nine series of experimental groups (n = 48), namely, Group I: Normal rats without tumor induction (Control “C”) (n = 3); Group II: Tumor-control (TC) (n = 3); Group III: T-treated glioma-induced rats “(T)” (n = 6); Group IV: M-treated glioma-induced rats “(M)” (n = 6); Group V: E-treated glioma-induced rats “(E)” (n = 6); Group VI: TM-treated glioma-induced rats (TM) (n = 6); Group VII: TE-treated glioma-induced rats (TE) (n = 6); Group VIII: ME-treated glioma-induced rats (ME) (n = 6) and Group IX: TME-treated glioma-induced rats (TME) (n = 6) as shown in Figure 1A . The dosage of the drugs, either alone or in combination, to be administered to the rats were selected based on our in vitro data and previous studies in glioma ( Fernandes et al, 2017 ; Yu et al, 2017 ; Piwowarczyk et al, 2020 ; Kuduvalli et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of combination therapy is to achieve a synergistic therapeutic effect using lower doses to lessen the toxicity of each agent, and to slow down the induction of drug resistance ( Chou, 2010 ; Zhao et al, 2020 ) since multiple signal pathways are targeted during the treatment. Previous research found that EGCG increased the efficacy of temozolomide and metformin in U87MG cells and rat C6 glioma cell lines, indicating that EGCG might be a useful adjuvant for cancer chemoprevention ( Kuduvalli et al, 2021 ). Recent literature suggests that HC synergizes with buthionine sulfoximine (BSO), a glutathione synthesis inhibitor to eliminate chronic myeloid leukemic (CML) cells through the GSH-ROS-JNK-ERK-iNOS mediated pathway ( Chowdhury et al, 2013 ) and reports have suggested that HC may be developed as a single-agent chemotherapeutic drug or as an adjuvant ( Gundala et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, employing drug repurposing approach, we had attempted to trigger apoptosis in glioma via ROS-mediated inactivation of PI3K/AKT/mTOR pathway (Yang et al, 2020). This was on grounds of our previous study, which proved that M and E synergistically enhanced the anti-glioma efficacy of T on C6 murine glioma and U-87 MG human glioblastoma cells by alleviating oxidative stress (Kuduvalli et al, 2021). Underpinning this idea, the current study was carried out to gain insight if the triple-drug combination (TME) could induce oxidative stress-mediated deactivation of PI3K/AKT/mTOR pathway and promote apoptosis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted on nine series of experimental groups (n=48), namely Group I: Normal rats without tumor induction (Control C) (n=3); Group II: Tumor-control (TC) (n=3); Group III: T-treated glioma-induced rats (T) (n=6); Group IV: M-treated glioma-induced rats (M) (n=6); Group V: E-treated glioma-induced rats (E) (n=6); Group VI: TM-treated glioma-induced rats (TM) (n=6); Group VII: TE-treated glioma-induced rats (TE) (n=6); Group VIII: ME-treated glioma-induced rats (ME) (n=6) and Group IX: TME-treated glioma-induced rats (TME) (n=6) as shown in Figure 1A . The dosage of the drugs, either alone or in combination, to be administered to the rats were selected based on our in vitro data and previous studies in glioma (Kuduvalli et al, 2021; Fernandes et al, 2017; Yu et al, 2017; Piwowarczyk et al, 2020).…”
Section: Methodsmentioning
confidence: 99%